Letter (copy) : Homes for Spanish orphans - Citrine, Walter, 1887-1983
030-0111-001 Secretary's. WMC/FC/DT/723. 21st July, 1938. Mr. E. Edwards, The Mineworkers' Federation of Great Britain, 50, Russell Square, LONDON, W.C.1. Dear Mr. Edwards, HOMES FOR SPANISH ORPHANS. I have received from Mr. Schevenels a copy of a provisional report which he has sent to you in regard to the above subject. No doubt this will be receiving the careful attention of your Sub-Committee, and I shall be glad to fix a further meeting if you think this will be helpful. Mr. Schevenels will be at Congress, and whilst it would not be possible for him to come here during the month of August, if you would like any further consultations before Congress some arrangements could be made for a talk on this subject. Yours sincerely, General Secretary. 292/946/30/111